2022
DOI: 10.3389/fcell.2022.1003028
|View full text |Cite
|
Sign up to set email alerts
|

A requirement for Krüppel Like Factor‐4 in the maintenance of endothelial cell quiescence

Abstract: Rationale and Goal: Endothelial cells (ECs) are quiescent and critical for maintaining homeostatic functions of the mature vascular system, while disruption of quiescence is at the heart of endothelial to mesenchymal transition (EndMT) and tumor angiogenesis. Here, we addressed the hypothesis that KLF4 maintains the EC quiescence.Methods and Results: In ECs, KLF4 bound to KLF2, and the KLF4-transctivation domain (TAD) interacted directly with KLF2. KLF4-depletion increased KLF2 expression, accompanied by phosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
2
6
0
Order By: Relevance
“…referred to as platelet endothelial cell adhesion molecule 1 (PECAM1), increased in both LV-treated ECs compared to the cells treated with phosphate-buffered saline (PBS) (Fig.1 G). The monomeric form of Klf-4 (Fig.2A; yellow arrow; ~75 kDa, as described by Mastej et al[16]) was upregulated only in LV-OSK-treated cells. Along with Klf-4 modulation, we observed the presence of histone H3 proteins (Fig.2 A; native H3, 15 kDa and 17-20 kDa).…”
supporting
confidence: 72%
“…referred to as platelet endothelial cell adhesion molecule 1 (PECAM1), increased in both LV-treated ECs compared to the cells treated with phosphate-buffered saline (PBS) (Fig.1 G). The monomeric form of Klf-4 (Fig.2A; yellow arrow; ~75 kDa, as described by Mastej et al[16]) was upregulated only in LV-OSK-treated cells. Along with Klf-4 modulation, we observed the presence of histone H3 proteins (Fig.2 A; native H3, 15 kDa and 17-20 kDa).…”
supporting
confidence: 72%
“…Research has demonstrated that KLF proteins exert strict regulatory control over the expression of mesenchymal markers. Specifically, the loss of KLF4 elevates the expression of collagens, VCAM-1, SMA, and SM22 in human lung ECs [ 47 ]. Moreover, KLF4 represses SM22 transcription during the phenotypic transition of smooth muscle cells via cooperatively binding with pELK-1 to the SM22 promoter [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our data puts forward a model by which primary cilia spatially control cushion growth through selective regulation of mechanosensitive factors. In this model, cilia dependent KLF4 expression is used to maintain endocardial quiescence, as has been seen previously 41 , thus providing an endocardial pool for replenishing differentiated luminal cells. Ciliated endocardium becomes Klf4 positive following the onset of blood flow, and then selectively deciliates in the high shear stress center of the AVC leading to reduced KLF4 (Fig.…”
Section: "Churning" Model For Early Valve Developmentmentioning
confidence: 97%
“…EndoMT is required for ECC development, and KLF4 has been shown to inhibit or activate EndoMT 22,[40][41][42][43] . To decouple KLF4's role in EndoMT, we examined the expression patterns of Vimentin (Vim, mesenchymal marker) and Kinase Insert Domain Receptor (Kdr, endothelial marker) to test whether KLF4-low cells in the center of the AVC were more or less likely to undergo EndoMT.…”
Section: Klf4 Expression Negatively Correlates With Cushion Endomt Pr...mentioning
confidence: 99%
See 1 more Smart Citation